1980
DOI: 10.1111/j.1365-2478.1980.tb01226.x
|View full text |Cite
|
Sign up to set email alerts
|

Dipole‐dipole Deep Geoelectric Soundings Over Geological Structures*

Abstract: ALFANO L. 1980, Dipole-Dipole Deep Geodectric Soundings over Geological Structures, Geophysical Prospecting 28,283-296.The dipole-dipole array is used for deep vertical gsoelectric soundings for practical reasons. However, the data obtained are often too scattered and the quality is lower than that of a Schlumberger sounding. The mathematical transform from these fields data to the corresponding Schlumberger ones is needed. It is demonstrated that for more general underground structures different from plane pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The improvement in ®eld technology and data processing has led to the successful use of the DC dipole±dipole method in structural studies of the earth's crust. Continuous polar dipole±dipole spreads (Alfano 1980) were used for resistivity imaging of geothermal ®elds (Risk, Caldwell and Bibby 1995;Monteiro, Andrade and Mendes 1997;Pe Ârez and Go Âmez 1997), volcanic areas (Giudici and Alfano 1997;Friedel et al 1998) and other geological structures at depths of some kilometres. Giudici and Alfano (1998) investigated vertical fault zones using magnetotelluric and DC electrical soundings.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement in ®eld technology and data processing has led to the successful use of the DC dipole±dipole method in structural studies of the earth's crust. Continuous polar dipole±dipole spreads (Alfano 1980) were used for resistivity imaging of geothermal ®elds (Risk, Caldwell and Bibby 1995;Monteiro, Andrade and Mendes 1997;Pe Ârez and Go Âmez 1997), volcanic areas (Giudici and Alfano 1997;Friedel et al 1998) and other geological structures at depths of some kilometres. Giudici and Alfano (1998) investigated vertical fault zones using magnetotelluric and DC electrical soundings.…”
Section: Introductionmentioning
confidence: 99%
“…To this purpose, we resorted to the transformation principle of axial dipole curves into equivalent half-Schlumberger' s ( M N fixed, A mobile). This test appears fully realizable because of the concurrence of the following circumstances : 1. the paper by Vedrintsev (1966) already quoted reports explicit formulas for the Schlumberger array; 2. when the sounding is parallel to the strike direction, no matter whether the array is in the internal or external regions, Schlumberger and half-Schlumberger soundings produce the same apparent resistivity curves; 3. the same occurs when the sounding is perpendicular to the strike with M N fixed in the midst of the internal region, and the two external regions have identical resistivities ( p i = p 3 ) ; 4. the transformation of axial dipole sounding curves into equivalent half-Schlumberger curves ( M N fixed, A mobile) is always possible for whatever underground structure (Alfano 1980, Patella 1981; 5. a very simple algorithm is available to transform numerically axial curves into half-Schlumberger curves (Patella 1974(Patella , 1981.…”
Section: Comparison W I T H Alpin's Resultsmentioning
confidence: 99%
“…Recent investigations have demonstrated that the adoption of the axial dipole configuration permits transformation into equivalent half-Schlumberger curves ( M N fixed and A mobile) even in the case of arbitrary underground structures (Alfano 1980, Patella 1981. Moreover, it has been proved that the transformation is an intrinsic smoothing, or low-pass filtering process, if applied to field dipole curves affected by " high-frequency " noise (Patella 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, square-wave signals are injected, because the signal can easily be recognized. Alfano (1980) imaged geological structures in dipole-dipole experiments. The longest measured profiles measure up to 22 km length: Storz et al (2000) imaged fault zones at the German continental deep-drilling site KTB (Kontinentale Tiefbohrung) and Schütze and Flechsig (2002) conducted such a profile across the flanks of the long valley caldera by using a large-scale dipole-dipole experiment to image fluid flow (Pribnow et al, 2003).…”
Section: Introductionmentioning
confidence: 99%